University-industry linkages and the role of the geographical proximity - Renato Garcia; Veneziano Araujo; Suelene Mascarini; Emerson Santos (European Regional Science Association (ERSA), 2011)
The main aim of this paper is to exam the local dimension of the university and industry linkages. It is widely recognized in the literature that academic research is an important source of new knowledge to the innovative efforts of the firms. Many authors, such as Audrescht and Feldman (1996), Acs and Varga (2005), Breschi and Lissoni (2009), have shown that academic research is positively correlated with firms' innovation at the geographical level. There are two reasons that are pointed out for this correlation. First, there are many ways in which knowledge generated by academic research can spill over to the firms, such as research papers, patents and informal contacts. Second, geographical proximity can encourage cooperation between academic researchers and the R&D staff in the firms. In this way, this paper tries to measure empirically the geographical dimension of the university-industry linkages in Brazil, in the same way to the first effort presented in ERSA 2010 (Garcia et al, 2010). To do that, it was used data from the Brazilian Research Council (CNPq), collected at the CNPq Directory of Research Groups of Brazilian universities. The data shows that in 2008 there were 22,797 research groups from 422 institutions. Among these research groups, 2,726 declared that they have interactions with more than 3,800 firms, which means 5,132 interactions between university and industry. Data were organized both in firm-level and in research group-level; allow the identification of the localization of the firm and of the research group. Among the 5,132 interactions between firms and research groups, it was possible to see that 43.6% of interactions occur inside the same city; 51.2% inside the same region; and 75.3% in the same state. These results show the importance of the local dimension of the interactions between academic research of the university and innovative efforts of the firms. In addition, it was done some empirical tests in order to identify the main factors that contribute to foster university-industry linkages.
Keywords: 330